Evaluasi Kinerja UMKM Dodol Ketan Mayang Makmur di Desa Teluk Rendah Kecamatan Tebo Ilir Kabupaten Tebo - Rogayah Rogayah; Siti Aminah (Jurnal MeA (Media Agribisnis), 2023)
This study aimed to determine : 1). description of the activities of Dodol Detan Mayang Makmur UMKM, Analyzing the income of Dodol Ketan Mayang Makmur UMKM and analyzing the feasibility of Dodol Ketan Mayang Makmur UMKM in Teluk Bawah Village, Tebo Ilir District, Tebo Regency. The research method used by researchers is the survey method. The results of this research are: 1) Management of Dodol Ketan Mayang Makmur UMKM consists of production activities and cost management. In production activities, the monthly capital used for the production of Sticky Dodol at Mayang Makmur Dodol Sticky UMKM is an average of IDR. 10,112,892 per month or per 15x production. This capital was used to purchase raw materials for sticky rice flour, white sugar, palm sugar, coconut milk, plastic with production reaching 15 kg per day with 15 times production. Or as much as 225 kg per month. The operational costs required per month used for the production of Dodol Sticky Rice are an average of IDR. 1o,112,892 per month. Meanwhile, employee salary costs per month are 4.5 million.